Predictability Limit of Monsoon Intraseasonal Precipitation: An Implication of Central Indian Ocean Mode - Qin, Jianhuang; Zhou, Lei; Ding, Ruiqiang; Li, Baosheng (Frontiers in Marine Science, 2022)
The prediction of monsoonal precipitation during Indian summer monsoon (ISM) remains difficult. Due to the high correlation between the Central Indian Ocean (CIO) mode index and the ISM precipitation variability, the predictability limit of the CIO mode index is investigated by the nonlinear local Lyapunov exponent (NLLE) method in observations. Results show that the predictability limit of the CIO mode index can reach 38 days during boreal summer (from June to September), which is close to the upper predictability limit of intraseasonal precipitation (up to 40 days), and higher than the predictability limits of dynamical monsoon indices (under 3 weeks) and boreal summer intraseasonal oscillation (BSISO) indices (around 30 days). Such high predictability limit of the CIO mode index is mainly attributable to the long predictability limits from the intraseasonal sea surface temperature (SST) and the meridional shear of background zonal winds ((∂u ̅)/∂y) over the ISM region. The former is one of the components of the CIO mode, and the latter is found to be the kinetic energy source of the CIO mode variabilities. As a result, the CIO mode is expected to extend the predictability of monsoonal precipitation, and benefits to improve the prediction skills of the ISM.